An urchin-like helical polypeptide-asparaginase conjugate with mitigated immunogenicity. (January 2021) - Hu, Yali; Wang, Dedao; Wang, Hao; Zhao, Ruichi; Wang, Yaoyi; Shi, Yunfei; Zhu, Jun; Xie, Yan; Song, Yu-Qin; Lu, Hua
Abstract: The use of asparaginase (ASNase), a first line drug for lymphoma treatment, is impaired by short circulation and notoriously high immunogenicity. Although PEGylation can prolong the circulating half-life of ASNase, however, it also induces anti-PEG antibodies that lead to accelerated blood clearance (ABC) and hypersensitivity reactions. Here, we create an urchin-like polypeptide-ASNase conjugate P(CB-EG3 Glu)-ASNase, in which the surface of ASNase is sufficiently shielded by an array of zwitterionic helical polypeptides through the labeling of the ε-amine of lysine. The conjugate is fully characterized with size exclusion chromatography, SDS-PAGE, dynamic light scattering, and circular dichroism. In vitro, P(CB-EG3 Glu)-ASNase retains full activity based on the enzymatic assay using the Nessler's reagent and cell viability assay. In vivo, examination of the enzyme activity in serum indicates that P(CB-EG3 Glu)-ASNase prolongs the circulating half-life of ASNase for 20 fold. Moreover, P(CB-EG3 Glu)-ASNase significantly inhibits tumor growth in a xenografted mouse model using human NKYS cells. Importantly, P(CB-EG3 Glu)-ASNase elicits almost no antidrug or antipolymer antibodies without inducing ABC effect, which is in sharp contrast with a similarly produced PEG-ASNase conjugate that develops both antidrug/antipolymer antibodies and profound ABC phenomenon. Our results demonstrate that urchin-like conjugates are outstanding candidates for reducing immunogenicity of therapeutic proteins, and P(CB-EG3 Glu)-ASNase holds great promises for the treatment of various lymphoma diseases. Graphical abstract: Image 1